Tiffany & Co: Omni-channel strategy for the Asian luxury consumer - REDDY, Srinivas K. (Institutional Knowledge at Singapore Management University, 2018)
Based in 2016, this case presents the dilemma faced by Tiffany & Co. (Tiffany), the luxury jewellery and specialty retailer, about embarking upon an omni-channel retail (OCR) strategy. Although Tiffany had a strong social media presence globally, it offered e-commerce solutions only in a few select markets. Online sales accounted for just six percent of its total sales, and there was limited integration between its brick-and-mortar outlets and online presence. While the company recognised the growing significance of OCR, as a luxury brand it struggled with the idea of embracing the online medium wholeheartedly. Luxury brands, synonymous with being superior, elusive and premium, endeavoured to provide a sensory-rich experience meant for a privileged few, while the online world was a mass media platform representing low cost, democratisation and a ubiquitous experience for all. The fashion-oriented and affluent Singapore market, with its high levels of internet usage and mobile penetration, provided a perfect opportunity for Tiffany to experiment with a fully integrated omni-channel strategy. However, it raised significant concerns too: What did implementing such a strategy mean in terms of investment in resources and capabilities? What would be the key factors to success? How would this strategy enable the brand to differentiate itself from other luxury brands? How would it impact Tiffany’s product lines, pricing strategies, store designs—physical and digital, service initiatives, and above all its brand equity? This case is designed for use by both undergraduate and postgraduate students. Students will learn about the key elements of an OCR strategy, and how it is different from a multiple channel approach. They will gain an understanding of the core values integral to luxury marketing, and their potential conflict with an OCR strategy; and be able to outline a suitable marketing strategy for successful implementation of OCR by a luxury brand.